Dynamic post-translational modification profiling of Mycobacterium tuberculosis-infected primary macrophages - Jonathan M Budzik; Danielle L Swaney; David Jimenez-Morales; Jeffrey R Johnson; Nicholas E Garelis; Teresa Repasy; Allison W Roberts; Lauren M Popov; Trevor J Parry; Dexter Pratt; Trey Ideker; Nevan J Krogan; et al. (eLife, 2020)
Macrophages are highly plastic cells with critical roles in immunity, cancer, and tissue homeostasis, but how these distinct cellular fates are triggered by environmental cues is poorly understood. To uncover how primary murine macrophages respond to bacterial pathogens, we globally assessed changes in post-translational modifications of proteins during infection with Mycobacterium tuberculosis, a notorious intracellular pathogen. We identified hundreds of dynamically regulated phosphorylation and ubiquitylation sites, indicating that dramatic remodeling of multiple host pathways, both expected and unexpected, occurred during infection. Most of these cellular changes were not captured by mRNA profiling, and included activation of ubiquitin-mediated autophagy, an evolutionarily ancient cellular antimicrobial system. This analysis also revealed that a particular autophagy receptor, TAX1BP1, mediates clearance of ubiquitylated Mtb and targets bacteria to LC3-positive phagophores. These studies provide a new resource for understanding how macrophages shape their proteome to meet the challenge of infection.